Circular movement of honey bee spermatozoa inside spermatheca. Issue 2 (3rd April 2018) - Tofilski, Adam; Chuda-Mickiewicz, Bożena; Czekońska, Krystyna
Abstract: It is believed that in honey bees spermatozoa stored inside the spermatheca remain motionless, however, some studies have reported the contrary. To observe behaviour of spermatozoa inside spermathecae, we have instrumentally inseminated queens with spermatozoa stained with fluorescent stains. During the first 8 h after insemination movement of the spermatozoa was stationary, without fast forward movement. Later, we observed circular movement of the spermatozoa inside spermathecae. Numerous circles were visible at one time. The circles were located close to the spermathecal wall. Movement of the spermatozoa was also observed in spermathecae of naturally inseminated queens. The marble-like pattern of the spermathecae was changing. The changes were slow and well visible only when video recordings were played at high speed.